INOVASI PEMBELAJARAN TECHNOPRENEURSHIP MELALUI IMPLEMENTASI MERDEKA BELAJAR-KAMPUS MERDEKA (MBKM) - Waziana, Winia; Novita Sari, Dita; Rahshel, Yeoyong; Herdiyan Saputra, Ricco; Andika Pratomo, Panji (Jurnal Abdi Insani, 2024)
The government's policy on the Merdeka Belajar Kampus Merdeka program aims to encourage students to master various fields of science and their fields of expertise so that they are ready to compete in the global world. This policy allows students to choose the courses they will take based on their wishes. The lack of practical competence of students, which is caused by learning with traditional methods centered on lecturers, is a problem raised in this activity so the innovation of Technopreneurship Through the Smart Farming Platform as an Implementation of Merdeka Belajar Kampus Merdeka (MBKM) is deemed necessary. The purpose of this PKm activity is to improve students' practical competence, by collaborating across fields of entrepreneur science with technology to prepare students to face the world of work dominated by technology. The research method applied in this activity is qualitative with a case study research type. The subjects of this research are students involved in the Smart Farming program as part of the MBKM program. This Pkm activity resulted in the Smart Farming program being implemented as part of MBKM, successfully bridging the gap between the academic world and the industrial world. Students are not only equipped with theoretical knowledge but also practical skills that are relevant to market needs.